STELLA—Potential European contributions to a NASA-led interstellar probe - Wimmer-Schweingruber, Robert F.; André, Nicolas; Barabash, Stanislav; Brandt, Pontus C.; Horbury, Timothy S.; Iess, Luciano; Lavraud, Benoit; McNutt, Ralph L.; Provornikova, Elena A.; Quémerais, Eric; Wicks, Robert; Wieser, Martin; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The discovery of a myriad of exoplanets in the past decades has revolutionized the understanding of our place in the universe. How different are exoplants and do some of them harbor life, just like Earth? To do so, their parent stars must drive a stellar wind and carve what we call astrospheres into the surrounding interstellar medium. Astrospheres are ubiquitous in our immediate neighborhood and show similar structure to our heliosphere. Voyager 1 & 2, Ulysses, Cassini, and IBEX have shown that the interaction between interstellar medium and solar wind is much more complex and involved than previously believed. This stellar-interstellar interaction is key to understand astrospheres and the shielding they provide to the planetary systems they harbor. This article summarizes a whitepaper that was submitted to NASA's 2023/2024 decadal survey which is being conducted by the US National Academies. It is based in parts on a proposal submitted to the European Space Agency (ESA) in response to its 2021 call for medium-class mission proposals. The whitepaper and this article propose to study the interaction described above in situ at the heliospheric boundaries and to explore the very local interstellar medium beyond. Furthermore, they highlight possible European contributions to a NASA-led Interstellar Probe (ISP).